Status of Major Nutrients in Acidic and Neutral Soils of Northern Hills Zone of Chhattisgarh State, India - Harinkhere, Sonali; Samadhiya, V.K.; Mishra, Mithun Kr.; Goswami, Rakesh Giri (Asian Journal of Chemistry, 2017)
This study was aimed to obtain rice genotypes that tolerant and sensitive to acid soil. This study was conducted in two different soil pH condition at farmer’s field at village Ajirma and research field at RMD College of Agriculture and Research Station Ajirma, Ambikapur, Chhattisgarh with twelve rice (Oryza sativa L.) genotypes laid out under randomized block design to identify the acid tolerant rice genotypes. Soil samples were collected from different locations of farmer’s field (pH 4.5) and research field (pH 6.6) and analyzed for some important physical and chemical properties, SOC and available N, P, K. Initially, at low pH condition SOC (0.27 %), N (151.6 kg ha-1), P (9.63 kg ha-1), K (148.06 kg ha-1) and at normal pH condition SOC (0.51 %), N (232.6 kg ha-1), P (14.89 kg ha-1), K (318.50 kg ha-1) were analyzed.